FLI1 in PBMCs contributes to elevated inflammation in combat-related posttraumatic stress disorder - Li, Pengfei; Liu, Liu; Liu, Shufeng; Lu, Zhongyang; Halushka, Perry V.; Sidles, Sara J.; LaRue, Amanda C.; Wang, Zhewu; Fan, Hongkuan (Frontiers in Psychiatry, 2024)
Post-traumatic stress disorder (PTSD) is a debilitating psychiatric condition with significant public health implications that arise following exposure to traumatic events.Recent studies highlight the involvement of immune dysregulation in PTSD, characterized by elevated inflammatory markers. However, the precise mechanisms underlying this immune imbalance remain unclear. Previous research has implicated friend leukemia virus integration 1 (FLI1), an erythroblast transformation-specific (ETS) transcription factor, in inflammatory responses in sepsis and Alzheimer's disease. Elevated FLI1 levels in peripheral blood mononuclear cells (PBMCs) have been linked to lupus severity. Yet, FLI1's role in PTSD-related inflammation remains unexplored. In our study, PBMCs were collected from Veterans with and without PTSD. We found significantly increased FLI1 expression in PBMCs from PTSD-afflicted Veterans, particularly in CD4 + T cells, with no notable changes in CD8 + T cells. Stimulation with LPS led to heightened FLI1 expression and elevated levels of inflammatory cytokines IL-6 and IFNγ in PTSD PBMCs compared to controls. Knockdown of FLI1 using Gapmers in PTSD PBMCs resulted in a marked reduction in inflammatory cytokine levels, restoring them to control group levels.Additionally, co-culturing PBMCs from both control and PTSD Veterans with the human brain microglia cell line HMC3 revealed increased inflammatory mediator levels in HMC3.Remarkably, HMC3 cells co-cultured with PTSD PBMCs treated with FLI1 Gapmers exhibited significantly lower inflammatory mediator levels compared to control Gapmertreated PTSD PBMCs. These findings suggest that suppressing FLI1 may rebalance immune activity in PBMCs and mitigate microglial activation in the brain. Such insights could provide novel therapeutic strategies for PTSD.